Tinjauan Pemeriksaan D-Dimer Pada Pasien Terkonfirmasi Coronavirus Disease 2019 di RSPTN-UH Makassar - Alfin Resya Virgiawan; Yaumil Fachni Tandjungbulu; Sahidan Sahidan; Guntur Baruara (Media Kesehatan Politeknik Makassar, 2023)
Covid-19 sufferers is often associated with coagulation disorders. Increased coagulation activation is caused by hyper inflammation and cytokine stormtriggered by the virus. This condition can cause venous thromboembolism. Tthe parameters ofcoagulation disorders is D-Dimer. This study aims to determine the results of D-Dimer examination in covid-19 sufferers. This type of research is a observational analitics study with a total of 150 research samples. The collection and examination of samples was carried out at the Clinical Pathology Laboratory of the Hasanuddin University State University Hospital in Makassar on May9th to June 6th, 2022. The results showed that the increased D-Dimer examination was obtained by 75 samples (50%) and the results of normal examinations as many as 75 samples (50%). Based on these results, it can be concluded that the D-Dimer levelssame as normal value. Keywords : Covid-19, D-Dimer, Makassar